Contribution of dietary intake to relapse rate in early paediatric multiple sclerosis. Issue 1 (9th October 2017) - Azary, Saeedeh; Schreiner, Teri; Graves, Jennifer; Waldman, Amy; Belman, Anita; Guttman, Bianca Weinstock; Aaen, Gregory; Tillema, Jan-Mendelt; Mar, Soe; Hart, Janace; Ness, Jayne; Harris, Yolanda; et al.
Abstract : Objective: The role of diet in multiple sclerosis (MS) course remains largely unknown. Children with MS have a higher relapse rate compared with MS in adults. Thus, studying the effect of diet on relapse rate in this age group is likely to provide more robust answers. Methods: This is a multicentre study done at 11 paediatric MS centres in the USA. Patients with relapsing-remitting MS (RRMS) or clinically isolated syndrome (CIS) with disease onset before 18 years of age and duration of less than 4 years were included in this study. Dietary intake during the week before enrolment was assessed with the validated Block Kids Food Screener. The outcome of the study was time from enrolment to the next relapse. 219 patients with paediatric RRMS or CIS were enrolled. Each 10% increase in energy intake from fat increased the hazard of relapse by 56% (adjusted HR 1.56, 95% CI 1.05 to 2.31, p=0.027), and in particular each 10% increase in saturated fat tripled this hazard (adjusted HR: 3.37, 95% CI 1.34 to 8.43, p=0.009). In contrast, each additional one cup equivalent of vegetable decreased the hazard of relapse by 50% (adjusted HR: 0.50, 95% CI 0.27 to 0.91, p=0.024). These associations remained with mutual adjustment and persisted when adjusting for baseline 25(OH) vitamin D serum level. Other studied nutrients were not associated with relapse. Conclusions: This study suggests that in children with MS, high energy intake from fat, especially saturated fat, may increase the hazard to relapse, while vegetable intake may be independently protective.